Use of whey protein, combined or not with vitamin D and resistant exercise in the treatment of sarcopenia in older adults: an integrative review (Research, Society and Development, 2022)
To perform an integrative review on the use of whey protein, combined or not with vitamin D supplementation and resistance exercise in the improvement of sarcopenia parameters in older adults. This is an integrative review study carried out in the MedLine, Virtual Health Library and PubMed databases, in which randomized, double-blind, controlled and multicenter clinical trials were selectedTwelve studies that investigated the intervention in the control versus placebo groups were evaluated. Whereas 10 related the use of vitamin D-enriched whey protein and 2 studies evaluated the effects of whey protein. As for the association with resistance exercise (RE), 8 of these studies were associated with RE and 4 studies did not. Satisfactory results have been described in the effects of sarcopenia Z score, increase in muscle strength parameters, muscle mass, fat-free mass and physical performance. There are benefits of isolated whey protein supplementation in improving muscle mass, strength and physical performance in elderly patients with sarcopenia, when combined with vitamin D. Protein supplementation associated with RE showed advantageous results for sarcopenia in aging, potentiated with the effect of supplementation.